2008
DOI: 10.1215/15228517-2008-054
|View full text |Cite
|
Sign up to set email alerts
|

Selective distribution of protein kinase A regulatory subunit RIIα in rodent gliomas

Abstract: Differential diagnosis of brain tumor types is mainly based on cell morphology and could benefit from additional markers. The cAMP second-messenger system is involved in regulating cell proliferation and differentiation and is conceivably modulated during cancer transformation. The cAMP second-messenger system mainly activates protein kinases, which are in part docked to cytoskeleton, membranes, or organelles by anchoring proteins, forming protein aggregates that are detergent insoluble and not freely diffusib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…No viable cultures were obtained from MB. GBM culture showed the same R2 clustered distribution restricted to the Golgi apparatus, as already described [9]. A similar restricted distribution was present in Ewing's sarcoma cultures, while R1 was present in the whole cytoplasm (Fig.…”
Section: Resultssupporting
confidence: 83%
“…No viable cultures were obtained from MB. GBM culture showed the same R2 clustered distribution restricted to the Golgi apparatus, as already described [9]. A similar restricted distribution was present in Ewing's sarcoma cultures, while R1 was present in the whole cytoplasm (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Forskolin and the xanthines, which act through the cAMP-producing and degrading enzymes to increase cAMP production in the cell, also showed an overall effect of increasing cell mortality. Immunocytochemistry showed that R2 was present in the all four human GBM cell lines ( Figure 3 ), as was already shown for mouse and rat GBM cells [ 15 ], and colocalized with the Golgi apparatus. The distribution of R2 was apparently modified during the cell cycle ( Figure 4 A,B,D).…”
Section: Resultssupporting
confidence: 78%
“…The highly expressed R2B is present in both neurons and glia, while R2A appears restricted to the ependymal cells [ 14 ]. In rodent and human glioma cells we observed a peculiar enrichment in R2A clusters, located at the Golgi apparatus, which are not present in healthy astrocytes within the brain [ 15 ]. As reported by other groups, we confirmed that activating the PKA system results in rodent glioma cell apoptosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…At variance with healthy brain tissue, in which RIalpha and RIIbeta are widely present in both soluble and insoluble fraction, these glioblastoma cells present a striking hotspot of insoluble RIIalpha in their Golgi apparatus; in addition, the interference with PKA activity leads these cells to apoptotic death [57] and is possibly correlated with genetic abnormalities on chromosome 7 and 17 [58]. These abnormalities span over the PKA RIalpha, RIbeta and RIIbeta-coding genes: in this way, the balance of PKA RI to RII subunits may be altered and may drive cells to tumorigenic phenotype.…”
Section: Involvement Of Pka Regulatory Subunits In Different Cancersmentioning
confidence: 99%